Assessment of wetland dynamics in Sirohi district of Rajasthan, India using remote sensing and GIS techniques - Navatha, K; Pattanaik, Chiranjibi; Reddy, C Sudhakar (Journal of Wetlands Ecology, 2011)
Wetlands are very dynamic ecosystems in the world. The present study provides scenario of wetlands of Sirohi district of Rajasthan, India. Landsat TM data of October, 1992, IRS-P6 LISS-III data of October 2005 and IRS-P6 AWiFS data of January, February, March, April and May months (2005) have been used in the study. Visual interpretation technique was adopted to map the areal extent of wetlands on 1:50,000 scale. Wetlands were classified following the Ramsar classification. The total extent of wetlands for the Sirohi district as a whole is estimated to 11,961 ha with representation 189 wetlands during 1992 which later decreased 11,307 ha in 2005 with a loss of 654.2 ha during 13 years. Of the total wetland area of the district, rivers accounted for 61.9% area, followed by reservoirs (15.1%), seasonal lakes (15%), perennial lakes (5.6%), and ponds (2.5%). Further it is also observed that drastic reduction in the water spread area from February to May months. For conservation of wetlands it is necessary to assess the changes which take place in the water bodies from time to time. Key words: GIS; Rajasthan; Remote sensing; Sirohi district; Wetlands DOI: http://dx.doi.org/10.3126/jowe.v5i0.4996 J Wet Eco 2011 (5): 66-72